The current situation and the directions of changes in rail freight transport in Thailand - Thammanoon Hengsadeekul; Thitirat Chaosakul; Rattapoohm Parichatprecha; Paveerat Pakdeenarong (My University, 2024)
The purpose of the article is to present the current situation in the rail freight transport in Thailand and the direction of changes in this area. Firstly, Thailand statistics in volume of freight transport by rail and modal share of freight transport have been presented. Afterwards, problems and obstacles in railway operational practices and in using rail transport services have been identified to improve railway system in Thailand and the outcome was assessed in terms of railway capacity and utilization. The findings were used to outline the direction of changes in rail freight transport. The results show that the rail transport capacity in double-track would increase by 48% (at present by 15.5% and as plan by 30%) and the ratio by rail transport to total freight transport would increase from at present by 1.87% to 10% in 2037.
Keywords: Rail freight transport; Maritime Ports and Logistics